Between Theory and Practice: Exploring Lecturers’ Perceptions on the Critical Literacy Approach in Critical Reading Classes - Fentry Hernaningsi Ruing; Baso jabu; Sultan Baa (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study explores university lecturers’ perceptions and experiences in implementing the Critical Literacy Approach (CLA) in teaching Critical Reading within the context of Indonesian higher education. In contrast to most previous research that focused on students’ learning outcomes or curriculum design, this investigation centers on lecturers’ pedagogical agency and their contextual adaptations of CLA. Using a descriptive qualitative case study design, three lecturers from different universities participated in in-depth interviews and semester-long classroom observations. Thematic analysis revealed that lecturers’ entry into critical literacy emerged through distinct pathways: self-directed study, reflective classroom practice, and formal graduate education. These trajectories informed how each lecturer interpreted and modified CLA that ranging from integrating discourse analysis and media literacy to using literature for social critique. Despite methodological variations, all lecturers shared a strong commitment to cultivating students’ critical thinking and sociopolitical awareness. However, the implementation was not without challenges: emotional discomfort around sensitive topics, student disengagement, and limited instructional time frequently emerged. Even so, the lecturers employed adaptive strategies to sustain dialogue and scaffold critical reflection. These findings highlight that effective CLA practice depends not only on theoretical understanding but also on emotional intelligence, contextual sensitivity, and institutional support. By foregrounding lecturers’ voices, this study contributes a practice-oriented perspective on critical literacy, urging a reorientation of research and policy to recognize educators as key agents of critical pedagogy in Indonesian higher education.